Improving loading amount of nanodendrite array photo-electrodes on quantum dot sensitized solar cells by second electrochemical deposition. (January 2022) - Wang, Meng; Peng, Zhuoyin; Huang, Dong; Ning, Zuoqiu; Chen, Jianlin; Li, Wei; Chen, Jian
Abstract: A second electrochemical deposition process is employed for TiO2 nanodendrite based quantum dot sensitized solar cells, which is anticipated to improve the quantum dot loading amount of the solar cells. The quantum dot loading amount is modulated by different electrochemical deposition time. The UV–vis and photoluminescence spectra of different photo-electrodes are investigated, which have exhibited the better optical absorption property and stable charge separation property after second electrochemical deposition process. Meanwhile, the current density of TiO2 nanodendrite based quantum dot sensitized solar cells has been obviously improved with the increasing of quantum dot loading amount. With the second electrochemical deposition of 30 min, the CuInS2 quantum dot sensitized TiO2 nanodendrite solar cells have exhibited the photovoltaic conversion efficiency enhancement from 3.91% to 4.58%.